The effect of kersen's skin infusion (Muntingia calabura L.) on blood uric acid levels of the rats (Rattus novergicus) - Asril Burhan; Usmar Usmar; Zulham Zulham; Ana Andarwiyati (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Background: Uric Acid or Gout is the results of purine metabolism, i.e. the enzymatic reshuffle of body cells from dinucleotide or ribonucleotide acids. High uric acid levels can be settled in the central joints and mesenchymal tissues such as the kidney.Objective: To determine an effect of administering the Kersen's (Muntingia calabura L.) ripe skin infusion against uric acid levels in the rats which have been induced with caffeine.Methods: Eighteen rats was divided into six groups, i.e. three as a control group (negative, positive and normal) and three as a treatment group (0,5%, 1%, and 2% doses). The measurements of blood uric acid levels were performed before induction, after induction and after treatment on 9th, 12nd, and 15th days. Results: There was a reduction of the uric acid levels in the rats which administered by ripe Kersen's fruit skin infusion at 1% with 3,43 mg/dL and 2% with 3.32 mg/dL doses. However, this reduction is not equivalent to the effect of allopurinol control decreased at 2.9 mg/dL. Statistical analysis results with Complete Randomized Design (RAL) revealed that positive control group, infusion in 1% and 2% dose did not have a significant difference with normal controls, that means allopurinol and both doses test give an effect to return the uric acid to normal conditions.Conclusion: The ripe Kersen's (Muntingia Calabura) fruit skin infusion provides a reduction effect on blood uric acid levels in the rats (Rattus Novergicus) that have been induced by caffeine. Concentration of infusion that reduced effect of blood uric acid levels in the rats are at 1% ( 1 g/ 200 gBW) and 2% (2 g/200 gBW). However, the reduction is not equivalent to the positive control of Allopurinol.